Folic Acid as a Potential Therapeutic Agent for Alzheimer's Disease: Effects on Inflammatory Cytokines, Amyloid Deposition, and Neurotransmitter Metabolism - Jing, Shaowei; Wang, Yanqiu; Liu, Yang; Luo, Yi; Wen, Xiaoqing; Ma, Yao; Zhu, Haoxuan; Chen, Gongcai; Ouyang, Xiaochun (Journal of Medical Biochemistry, 2025)
Objective: Alzheimer's disease (AD) is a degenerative disease of the central nervous system characterized by neuroinflammation and amyloid deposition. Folic acid (FA), a B vitamin, may improve the course of AD by modulating inflammation and neuroprotection. The aim of this study was to investigate the effects of FA supplementation on serum inflammatory cytokines (IL-1β, IL-6, TNF-α), amyloid (Aβ1-42), Tau proteins, and neurotransmitters (GABA, 5-HT, Ach) in AD patients.Methods: 114 AD patients were included and randomly divided into control group (donepezil treatment) and experimental group (donepezil + folic acid treatment) for 3 months. Inflammatory factors, Aβ1-42, Tau, neurotransmitter levels and nutritional status were assessed before and after treatment.Results: The total effective rate of the experimental group (89.47%) was significantly higher than that of the control group (75.44%), and the levels of inflammatory factors (IL-1β, IL-6, and TNF-α), Aβ1-42, and Tau were significantly lower (P
Keywords: Alzheimer's disease; Inflammatory Cytokines; Folic acid; Neurotransmitters; Aβ1-42